Une méthode pour évaluer les curricula d’éducation au changement climatique dans une visée transformative - Frédéric Leterme; Angela Barthes; Nicole Mencacci (Éducation et Socialisation)
In the time of the Anthropocene (Wallenhorst & Wulf, 2024), we start from the hypothesis that of the four possible educational goals proposed by Lange (2020), societal transformation is the one needed to achieve the objectives of the Paris Agreement. Accordingly, we propose a method for evaluating climate change education curricula based on a transformative example drawn from a climate negotiation simulation dossier supported by the French development agency and the Office for Climate Education (AFD & OCE, 2023). Traditionally, assessments of learners in a school context are carried out through learner-centered skills. We argue that, given the climate emergency in the Anthropocene, a shift in the evaluative paradigm is required. We propose a new evaluation model based on externalities (Barthes & al., 2024) related to the fight against climate change, where the learner is evaluated based on their impact on the world. We also demonstrate how Lahire's dispositions (2005, 2012) concepts allow both the assessment of the transformative potential of climate curricula and the inclusion of broader evaluation criteria for learners, grounded in externalities within the climate emergency context. This work is part of the research on the necessary paradigm shifts in the evaluation of " cross-cutting education " (Mencacci & Barthes, 2023, 2024).